Tourism versus spatial order: mutual relations - Meyer, Beata (Turyzm/Tourism, 2012)
The relation between tourism and the spatial environment is characterized by mutual interaction. The proliferation of tourism and massive tourism development intensifies its impact on the spatial environment, yet the focus is usually placed on environmental degradation and the resulting distortion of spatial order. Concurrently, the significance of the spatial environment, and spatial order in particular, as one of the determinants of tourism development is understated. On a theoretical plane the relation seems obvious, yet once the practical dimension is considered, it becomes at least debatable.